Programming with Microsoft Visual basic 2008 : - Ekedahl, Michael (Course Technology, 2010)
Programming with MICROSOFT? VISUAL BASIC 2008: AN OBJECT-ORIENTED APPROACH, Third Edition is designed for individuals with little or no programming background. In this edition, each chapter is divided into two lessons - Concept and Application. The Concept lesson appears first. Software design and programming concepts appear in this section. In the Application lesson, you will find the design and implementation of a real-world application, along with limited hands-on steps to complete that application.